Relationships among supervisor support, autonomy, job satisfaction and emotional labor on nurses within the Turkey context of healthcare services - Altaş, Sabiha Sevinç; Gündüz Çekmecelioğlu, Hülya; Konakay, Gönül; Günsel, Murat (Frontiers in Psychology, 2024)
Healthcare professionals face the challenging task of regulating their emotions within the workplace, which can lead to significant pressure and stress. For nurses, who work in particularly demanding environments, fulfilling the expectations of emotional labor can be challenging. This study explores how nurses' perceptions of supervisor support and job autonomy can positively influence emotional labor and job satisfaction. Job autonomy is found to negatively affect emotional labor but positively impact job satisfaction. Additionally, job satisfaction is a significant precursor to both surface and deep-acting dimensions of emotional labor. Furthermore, job satisfaction mediates the relationship between supervisor support and deep-acting emotional labor, as well as between job autonomy and both surface and deep-acting emotional labor. These findings shed light on the complex dynamics of emotional labor and job satisfaction in healthcare settings.